2021
DOI: 10.5704/moj.2107.014
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Rich Plasma Injection for Soft Tissue Musculoskeletal Pain

Abstract: Introduction: Treating soft tissue injuries can be a challenge for physicians as it can be overlooked which can lead to more problems. In recent studies, the use of Platelet Rich Plasma (PRP) has been gaining popularity for soft tissue injuries because of its benefits and minimal side effects. This study aims to evaluate the effect of PRP injection on various musculoskeletal soft tissues inflammation. Material and Methods: This is a retrospective study of patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…At four weeks after the intervention, the mean VAS score decreased from 6.8 ± 1.2 (the baseline) to 3.2 ± 1.5, and at eight weeks, it decreased to 2.1 ± 1.0. These findings are consistent with previous studies that have demonstrated the potential analgesic effects of PRP in various musculoskeletal conditions [13][14][15]. The proposed mechanism involves the release of platelet growth factors, modulating inflammation, and promoting tissue repair [16].…”
Section: Discussionsupporting
confidence: 92%
“…At four weeks after the intervention, the mean VAS score decreased from 6.8 ± 1.2 (the baseline) to 3.2 ± 1.5, and at eight weeks, it decreased to 2.1 ± 1.0. These findings are consistent with previous studies that have demonstrated the potential analgesic effects of PRP in various musculoskeletal conditions [13][14][15]. The proposed mechanism involves the release of platelet growth factors, modulating inflammation, and promoting tissue repair [16].…”
Section: Discussionsupporting
confidence: 92%
“…While promising, PRP is invasive and time-consuming. PRP requires the injured person to undergo a series of blood withdrawals, platelet enrichment of the blood samples, and reinjection of the fractionated plasma into the injury site [ 22 , 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%